সামটা : আর্সেনিক দূষণে আক্রান্ত একটি গ্রাম - পারভীন, মনজুয়ারা, ১৯৭১- (ঢাকা : ইউনিভার্সিটি প্রেস লিমিটেড, 2013)
On ground water contamination with Arsenic and related health issues, chiefly with reference to Sāmaṭā, a village in Jessore District, Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Arsenic -- Toxicology; Arsenic -- Health aspects; Drinking water -- Arsenic content -- Bangladesh -- Sāmta; Groundwater pollution -- Bangladesh -- Sāmta; Arsenic -- Health aspects -- Bangladesh -- Sāmta; Arsenic -- Toxicology -- Bangladesh -- Sāmta